Microbial community roles and chemical mechanisms in the parasitic development of Orobanche cumana. Issue 3 (13th June 2022) - Xi, Jiao; Lei, Beilei; Liu, Yong‐Xin; Ding, Zanbo; Liu, Jiaxi; Xu, Tengqi; Hou, Lijun; Han, Siqi; Qian, Xun; Ma, Yongqing; Xue, Quanhong; Gao, Jinming; et al.
Abstract: Orobanche cumana Wallr. is a holoparasite weed that extracts water and nutrients from its host the sunflower, thereby causing yield reductions and quality losses. However, the number of O. cumana parasites in the same farmland is distinctly different. The roots of some hosts have been heavily parasitized, while others have not been parasitized. What are the factors contributing to this phenomenon? Is it possible that sunflower interroot microorganisms are playing a regulatory role in this phenomenon? The role of the microbial community in this remains unclear. In this study, we investigated the rhizosphere soil microbiome for sunflowers with different degrees of O. cumana parasitism, that is, healthy, light infection, moderate infection, and severe infection on the sunflower roots. The microbial structures differed significantly according to the degree of parasitism, where Xanthomonadaceae was enriched in severe infections. Metagenomic analyses revealed that amino acid, carbohydrate, energy, and lipid metabolism were increased in the rhizosphere soils of severely infected sunflowers, which were attributed to the proliferation of Lysobacter . Lysobacter antibioticus (HX79) was isolated and its capacity to promote O. cumana seed germination and increase the germ tube length was confirmed by germination and pot experiments. Cyclo(Pro‐Val), an active metabolite of strain HX79, was identified and metabolomic and molecular docking approaches confirmed it was responsible for promoting O. cumana seed germination and growth. And we found that Pseudomonas mandelii HX1 inhibited the growth of O. cumana in the host rhizosphere soil. Our findings clarify the role of rhizosphere microbiota in regulating the parasite O. cumana to possibly facilitate the development of a new weed suppression strategy. Highlights: Parasitic weed growth is influenced by microbes in the sunflower rhizosphere. The germination of Orobanche cumana seeds can be facilitated by Lysobacter antibioticus HX79 metabolites. The molecular docking strategy can be used for screening active chemicals. Abstract : Parasitic weed growth is influenced by microbes in the sunflower rhizosphere. The germination of Orobanche cumana seeds can be facilitated by Lysobacter antibioticus HX79 metabolites. The molecular docking strategy can be used for screening active chemicals.